The Impact of Long COVID on Global Public Health: Long-term Consequences and Healthcare System Preparedness - Wahyudi, Andi (Magenta Journal De Healthymedi, 2024)
Long COVID, or Post-Acute Sequelae of SARS-CoV-2 infection (PASC), is an emerging global public health challenge. This study aims to quantitatively assess the prevalence, symptom profiles, and long-term consequences of Long COVID while evaluating the preparedness of healthcare systems to manage its impact. A cross-sectional analysis was conducted on 5,000 individuals from high-, middle-, and low-income regions who experienced COVID-19. Results show that 30% of participants reported persistent symptoms, with fatigue (60%), cognitive impairment (45%), and shortness of breath (40%) being the most common. Long COVID disproportionately affected older adults, females, and those with pre-existing conditions. Furthermore, 50% of patients reported an inability to return to work, highlighting the condition’s significant economic burden. Healthcare utilization was high, with 70% of patients requiring outpatient visits and 45% needing rehabilitation services. However, healthcare system preparedness was found to be inadequate, particularly in low-income countries, where only 40% of patients had access to necessary care. Specialized Long COVID clinics and rehabilitation programs were the most effective interventions, with 60% of patients reporting improvement. These findings underscore the urgent need for healthcare system reforms and targeted interventions to address the long-term impacts of Long COVID.